Between the Sword and the Soul: Sufism’s Living Tradition of Jihād - Muhammad Jusuf Nur Ikhsan; Imam, Mohammad Fuyudun Niam (An-Nur International Journal of Islamic Thought, 2025)
This article explores the multidimensional understanding of jihād within the Sufi tradition, focusing on its typology as internal, verbal, and physical struggle (jihād al-nafs, jihād al-lisān, jihād al-Sayf). Drawing on classical Sufi texts, historical accounts, and modern scholarly analyses, the study re-evaluates the perception of Sufism as an exclusively pacifist movement. It argues that early Sufi thinkers such as Al-Ghazālī, Rūmī, and ʿAbdallāh b. al-Mubārak developed an integrated conception of jihād that prioritized spiritual purification but also permitted martial engagement under ethical conditions. The paper highlights the roles of Sufi saints and brotherhoods in resisting tyranny through speech, participating in holy wars, and supporting imperial military structures such as the Janissaries and Mughal armies. In modern times, many Sufi groups have reinterpreted jihād in nonviolent, ethical, and social terms, offering a counterbalance to Salafi-jihadist ideologies. The study concludes that Sufism’s legacy of combining inner discipline with outward responsibility provides a more holistic and historically grounded vision of jihād, one that continues to resonate in contemporary Islamic thought and global religious discourse.